ENT 530 Business Plan : Enchanted.Co / Muhammad Haikal Nadzri... [et al.] - Nadzri, Muhammad Haikal; Azman, Puteri Nurulaina; Mohd Rasman, Ainur Balqis; Jamaludin, Norish Jasmin; Ibrahim, Yusra Irhannan; Saiful Nizam, Farra Nurdeanna (2018)
Enchanted.co is a company that offers goods and services of crafting product from recycled clothes. It is located at No. 1-03, Jalan Medan Pusat Bandar 7A, Seksyen 9, 43650 Bandar Baru Bangi, Selangor. There are total of 12 workers that operates in this business. Other than the Chief Executive Officer, Financial Manager, Operations Manager, Administrative Manager and Fashion Designer. If the demand is too high, we will consider recruiting part time workers. Enchanted.co uses high quality of material and gives a lot of attention and care to produce our bags from the used materials. Therefore, all the products of our company are high in quality and has a bigger difference than other crafting business. Other than that, we also frequently make various kind of promotion to increase sales. Enchanted.co is a small-sized company that is trying to bring the love towards crafting back into the hearts of Malaysians. Taken the inspirations from the traditional crafting product, this company is bringing their own twist of urban touches into the crafting arts. Enchanted.co's slogan which is also their brand's name is "From O to 100 real quick" which is legitimately inspired by their aim and goals. Their products are innovative-value added that can offer various benefits to customers, besides offering them goods that could make their collections a whole lot better, enchanted.co also offers services that can solve their daily problems.